An internet of things-based medication validity monitoring system - Yasmin Makki Mohialden; Nadia Mahmood Hussien; Qabas Abdal Zahraa Jabbar; Mostafa Abduhgafoor Mohammed; Tole Sutikno (Institute of Advanced Engineering and Science, 2022)
Medicine is critical to our everyday lives and to the well-being of individuals of all ages and backgrounds. With the beginning of the Corona pandemic and a rise in Corona virus infection cases, the use of medications to prevent and recover from infection has increased, as well as to treat illness consequences, has grown. The effectiveness of medicines is greatly influenced by the expiration date. In this paper, a system for pharmacy or medical store's information storage system was developed and enhanced by automatically monitoring the validity of medications on a periodic basis and sending expiry reports to medicine authorities through e-mail to warn them that a medicine is approaching expiration. The system was also enhanced with internet of thing (IoT) for fast and secure delivery of the medicine validity report.